SOME PROPERTIES OF GENERALIZED EIGENFUNCTIONS OF ONE CLASS OF DIFFERENTIAL OPERATORS - Asatryan, H.A.; Sargsyan, T.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
In the paper considers continuality in a parameter of generalized eigenfunc-tions of one class of differential operators. Properties of one class of functions constructed by means of the generalized eigenfunctions and used in the theory of integral equations are studied.